A longitudinal study on the stability and causal relationships between disability acceptance, self‐efficacy, and interpersonal ability among Koreans with disability. Issue 3 (5th October 2022) - Kim, Eun Hye; Cui, Li Na; Nho, Choong Rai
Abstract: The purpose of this study was to explore the longitudinal, reciprocal effects between disability acceptance, self‐efficacy, and interpersonal ability and to discuss implications for persons with disability. For this purpose, we used the third (2018–2020) raw data of the second Panel Survey of Employment for the Disabled (PSED), implemented by the Korea Employment Agency for Persons with Disability. We used an autoregressive cross‐lagged model to test reciprocal effects, and 4420 persons with disability responded to the three above‐mentioned waves of the PSED. The findings were as follows. First, disability acceptance, self‐efficacy, and interpersonal ability had significant effects on disability acceptance, self‐efficacy, and interpersonal ability in the third, fourth, and fifth waves. Second, there was a statistically significant longitudinal, reciprocal relationship between disability acceptance and self‐efficacy. In addition, self‐efficacy had a significant longitudinal, reciprocal relationship with interpersonal ability. However, interpersonal ability had a statistically significant longitudinal effect on disability acceptance, but not vice versa. Based on these results, we provided suggestions regarding how to improve disability acceptance, self‐efficacy, and interpersonal ability among persons with disability.